A novel analytical method of windmill chiral cell structure (WCCS). (15th July 2021) - Qiu, Lifang; Yu, Yue; Zheng, Lin; Chen, Mingkun
Highlights: A new method for linear performance analysis based on stiffness matrix is proposed. The parametric model of a chiral material with twist degree of freedom is built. The effect of Multi-units on the performance is analyzed by this model. The new method is verified by the FEA (finite element analysis). Abstract: This paper proposes a novel analytical method based on a stiffness matrix. The static properties of a Windmill Chiral Cell Structure (WCCS) are evaluated using this method. The theoretical model for the WCCS, which with twist degree of freedom (DOF), is established by hierarchical construction, rigid constraints establishing and eliminating redundant nodes. The influence of different structural parameters on the DOF of WCSS is also investigated. Moreover, the correctness of the theoretical model is verified by the finite element analysis (FEA). The method can be applied to the analysis of linear properties of mechanical metamaterials and provide some reference for the 3D cellular structure design. The proposed WCCS structure can be used to make high precision rotary displacement stages.